Analysis of microstructure and wear resistance of NM400 thick plate. Issue 3 (March 2021) - Cong, Liang; Pei, Yingchao; Xia, Dianxiu; Wang, Dongyue; Han, Zhengpeng; Han, Qing; Liu, Zhiheng; Guo, Yu
Abstract: The hardness distribution and microstructure morphology of NM400 low alloy wear resistant steel plate with thickness of 50mm and 60mm were tested and analyzed, and the sliding wear performance of typical measuring points was also analyzed. The results show that the depth of the NM400 (50mm) hardening layer is about 35mm, accounting for about 70% of the plate thickness. The depth of the NM400 (60mm) hardening layer is about 22mm, accounting for about 37% of the plate thickness. With the position of the measuring point gradually away from the surface of the steel plate, the martensite content in the microstructure of NM400 (50mm) and NM400 (60mm) gradually decreased, and the contents of pearlite, bainite and other microstructure gradually increased. The hardness of NM400 (50mm) gradually decreased from 410HV to 335HV, and the hardness of NM400 (60mm) gradually decreased from 410HV to 305HV. The micro-wear morphologies of NM400 (50mm) and NM400 (60mm) at each measuring point are mainly furrow and contact fatigue spalling, and the wear types are mainly abrasive wear and contact fatigue wear. The furrow depth and the number of furrows on the worn surface of the sample at the corresponding measuring point position gradually increased as the measuring point position moved away from the steel plate surface, and the spalling area and the depth of the spalling pit gradually increased. The wear type gradually changed from particle wear to contact fatigue wear.